2016
DOI: 10.1093/jac/dkw227
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of KPC-encoding plasmids from two endemic settings, Greece and Italy

Abstract: pKpQIL-like plasmids played a major role in the dissemination of blaKPC in Greece and Italy, but evolved with different dynamics in these endemic settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 50 publications
6
36
0
2
Order By: Relevance
“…Other rearrangements of the pKpQIL backbone have also been reported elsewhere (12, 13, 16), indicating the dynamic genetic nature of this plasmid and suggesting that these variants may be the result of selection for adaptation to the host in a niche environment.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Other rearrangements of the pKpQIL backbone have also been reported elsewhere (12, 13, 16), indicating the dynamic genetic nature of this plasmid and suggesting that these variants may be the result of selection for adaptation to the host in a niche environment.…”
Section: Introductionsupporting
confidence: 70%
“…Although the bla KPC carbapenemase can be found in various Enterobacteriaceae (22), it is predominantly associated with K. pneumoniae and the pKpQIL plasmid (7, 24). This plasmid has a high propensity for genetic rearrangements (12, 13, 16), but the benefit of such genetic plasticity and consequences of evolution of the plasmid in relation to different hosts remain unclear. Here, we investigated whether the pKpQIL-D2 plasmid confers a different fitness impact to that of the more widely observed pKpQIL-UK plasmid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pBK30661 was identified as an IncFIA plasmid harboring nine ARGs for β‐lactam resistance ( bla KPC‐3 , bla TEM‐1 , bla OXA‐9 ), aminoglycoside resistance ( aacA4 , aadA1 , strA , strB ), sulfonamide resistance ( sul2 ), and trimethoprim resistance ( dfrA14 ) . Other IncF types, such as pKP1504‐KPC and pGR‐1780, have also been reported to spread bla KPC‐2 in K. pneumoniae clinical isolates, specifically isolates ST258 and ST147 …”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 99%
“…To our knowledge, this is the first report on complete sequences of IncR plasmids carrying Tn4401a transposon. However, previous studies have reported the presence of multireplicon IncFII K2 -IncR KPC-2-encoding plasmids from ST101 K. pneumoniae isolated in Italian hospitals (31,32). In addition, type B plasmids were derivatives of type A IncR bla KPC-2positive plasmids carrying an IncN3-derived segment.…”
mentioning
confidence: 93%